Juvenile idiopathic arthritis - Krupa H Bhatt; Freny R Karjodkar; Kaustubh Sansare; Darshana Patil (Wolters Kluwer Medknow Publications, 2014)
Juvenile Idiopathic Arthritis (JIA) is the most chronic musculoskeletal disease of pediatric population. The chronic course of disease has a great impact on oral health. Temporomandibular joint is involved in JIA causing limited mouth opening with progressive open bite, retrognathia, microgenia and bird like appearance. Joints of upper and lower extremities are also involved. Effect on upper limb function leads to difficulty with fine motor movements required for brushing and flossing. This increases incidence of caries and periodontal disease in children. The cause of JIA is still poorly understood and none of the available drugs for JIA can cure the disease. However, prognosis has improved as a result of progress in disease classification and management. The dental practitioner should be familiar with the symptoms and oral manifestations of JIA to help manage as multidisciplinary management is essential.